Solution of Coupled System of Caputo Fractional Differential Equations with Multi-Point Boundary Conditions - M. Jameel, Saif Aldeen; Ndiaye, Ameth (Al-Nahrain Journal of Science, 2024)
This article relies on the Caputo fractional derivative for the objective of is to examine an interconnected system of fractional differential equations. The problem under consideration involves four fractional-Caputo-derivatives underneath initial conditions. We state and prove the existence and uniqueness theorem of solution by application of Banach fixed point theorem. Then, another result that deals with the existence of at least one solution is delivered and some sufficient conditions for this result are established by means of the fixed-point theorem of Schaefer. We end the paper by presenting to the reader by illustrative example.